TINJAUAN ANALISIS TAFSIR AHKKAM TENTANG UTANG PIUTANG (AL-QUR’AN SURAT AL-BAQARAH AYAT 282) - Ikmal Mumtahaen (Fakultas Hukum Universitas Malikussaleh, 2023)
Debt is one of the activities that may not be separated from society, this is to solve problems in the economic field. However, in carrying out these debt transactions, the community often ignores the principle of prudence, one of which is recording or procuring witnesses in carrying out these debts. In terms of setting aside witnesses and records, this will have an impact on proving if one day there is a dispute in settlement of debts. So thus the author tries to raise Q.S al-Baqarah verse 282 which according to the author has a close relationship with the basis of non-cash transactions. The method used in this writing is a qualitative method, namely the author takes primary data from Q.S al-Baqarah verse 282 and analyzes it with the help of secondary data, namely all data that supports the problem being studied. After the data is analyzed, it is then described using qualitative methods, namely describing the results of the research in words. From the results of research on the analysis of Q.S al-Baqarah verse 282, the author gets a common thread regarding the obligation to record debt transactions, besides there are sentences that identify obligations, this verse has a correlation with evidence in terms of Civil Procedure Law in Indonesia.